ARTIFICIAL INTELLIGENCE IN MARKETING: NEW METHODS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
In the article, the author outlines the degree of influence of artificial intelligence on the economy and business, and also examines its opportunities and problems.